Boredom in Legal Education - Slovenko, Ralph (1960)
The law school should strive to educate the lawyer and nonlawyer not only on law but also on society. In this enterprise, there will be no boredom. Law, viewed as an interplay of history, logic, and sociology, is second to none as an exciting and liberal subject